Management of perioperative myocardial ischaemia after isolated coronary artery bypass graft surgery - Davorin Sef; Janko Szavits-Nossan; Mladen Predrijevac; Rajna Golubic; Tomislav Sipic; Kresimir Stambuk; zvonimir korda; Pascal Meier; Marko Ivan turina (Open Heart)
Objectives Updated knowledge about perioperative myocardial ischaemia (MI) after coronary artery bypass grafting (CABG) and treatment of acute graft failure is needed. We analysed main factors associated with perioperative MI and effects of immediate coronary angiography-based treatment strategy on patient outcome.Methods Among 1119 consecutive patients with coronary artery disease who underwent isolated CABG between January 2011 and December 2015, 43 (3.8%) patients underwent urgent coronary angiography due to suspected perioperative MI. All the data were prospectively collected and retrospectively analysed. The primary endpoint was 30-day mortality; postoperative left ventricular ejection fraction) and major adverse cardiac events were secondary endpoints.ResultsOverall, 30-day mortality in patients with CABG was 1.4% while in patients who developed perioperative MI was 9% (4 patients). Angiographic findings included incorrect graft anastomosis, graft spasm, dissection, acute coronary artery thrombotic occlusion and ischaemia due to incomplete revascularisation. Emergency reoperation (Redo) was performed in 14 (32%), acute percutaneous coronary intervention (PCI) in 15 (36%) and conservative treatment (Non-op) in 14 patients. Demographic and preoperative clinical characteristics between the groups were comparable. Postoperative LVEF was significantly reduced in the Redo group (45% post-op vs 53% pre-op) and did not change in groups PCI (56% post-op vs 57% pre-op) and Non-op (58% post-op vs 57% pre-op).Conclusions Urgent angiography allows identification of the various underlying causes of perioperative MI and urgent treatment when this is needed. Urgent PCI may be associated with improved clinical outcome in patients with early graft failure.